2021
DOI: 10.2174/1874210602115010160
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Utilization of Bulk-Fill Composites among Dental Practitioners in Saudi Arabia

Abstract: Objective: The aim of this study was to assess the knowledge and utilization of Bulk-Fill (BF) resin composites among dental practitioners in Saudi Arabia. Materials and Methods: An online survey was distributed through Twitter, Instagram and WhatsApp applications among dentists in Saudi Arabia. A 31-item questionnaire covering personal data, general knowledge and utilization of BF composites was used. Responses were collected and analyzed for trends. A knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Thus, the longer experience duration that NGDs had in this study didn't increase their reported knowledge of SDCs existence or their respective utilization in dental practice. A study by Nassar et al, reported a similar absence of clinical experience positive effect on the dentists' use of new bulk fill restorative resin materials [30].…”
Section: Discussionmentioning
confidence: 94%
“…Thus, the longer experience duration that NGDs had in this study didn't increase their reported knowledge of SDCs existence or their respective utilization in dental practice. A study by Nassar et al, reported a similar absence of clinical experience positive effect on the dentists' use of new bulk fill restorative resin materials [30].…”
Section: Discussionmentioning
confidence: 94%
“…The earliest clinically visual manifestation of dental caries is known as white spot lesion (WSL) as it has a distinct chalky opaque appearance on enamel that is caused by a bacterial-acid-induced increase in the porosity of the superficial enamel layer [6,7]. At this stage and prior to frank cavitation of the tooth structure, several therapeutic measures can be applied to reverse or arrest the lesion [6,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Restorative treatment of the detrimental effects of dental caries in the oral cavity by merely replacing lost dental hard tissues takes a major toll on healthcare services worldwide [10][11][12]. Current dental practices aim at dealing with dental caries as a whole by focusing on prevention and possible reversal of the entire process, rather than merely managing the disease's manifestations by artificially restoring resultant dental defects [8,13,14]. Even though the diagnosis of dental lesions is only one aspect of the disease's management plan, rigorous procedures resulting in early detection and long-term monitoring of carious WSLs is paramount to its success [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%